99mTc-labeled iRGD for single-positron emission computed tomography imaging of triple-negative breast cancer - Yu, Buhui; Su, Hongxing; Zhao, Lingzhou; Yang, Jiqin; Zhu, Meilin; Zhao, Jinhua (Frontiers in Bioengineering and Biotechnology, 2022)
Triple-negative breast cancer (TNBC) is the most aggressive breast cancer subtype, with a high mortality rate. One of the main reasons for this poor prognosis is the failure of a specific diagnosis. As a tumor-homing and penetrating peptide, iRGD has not only the properties of binding to neuropilin-1 and integrin αvβ3 but also internalizing into TNBC cells. In this study, we designed and prepared 99mTc-labeled iRGD (99mTc-HYNIC-iRGD) as a single-positron emission computed tomography (SPECT) imaging probe and investigated its feasibility for the targeted diagnosis of TNBC. The results showed that the iRGD peptide had acceptable biocompatibility within the studied concentration range and could specifically bind to TNBC cells in vitro. The 99mTc-HYNIC-iRGD was readily prepared with high radiochemical purity and stability. SPECT imaging of 99mTc-HYNIC-iRGD in a TNBC tumor-bearing mouse model showed obvious tumor accumulation with rapid blood clearance and favorable biodistribution. Our findings indicate that this active-targeted strategy has great potential to be developed as a novel tool for TNBC imaging.